THERMO-VISCOELASTIC CHARACTERIZATION OF POLYMER LAMINATE FILMS - Eliza Truszkiewicz; Daniel Tscharnuter; Gerald Pilz (Acta Polytechnica CTU Proceedings)
The investigated material - laminate is intended as a substrate for small electronic components, electrodes and printed circuits, which are processed onto the laminate prior to thermoforming. The placement of the electronic components and the connecting circuits must be carefully designed to prevent damage during the thermoforming. The thermo-viscoelastic behavior of a polymer laminate film was characterized by mechanical measurements to obtain data for material modeling. The strain was measured using digital image correlation. The film is anisotropic and is able to deform to strains up to 60%.